Induction of experimental hyperglycemia in mollusc Lymnaea stagnalis after animal’s incubation in high-concentrated glucose solution - Shadenko, Victoria N.; Sidorov, Alexander V. (Experimental Biology and Biotechnology, 2019)
We established that two hours’ long exposition of molluscs in 100 mmol/L glucose water solution results in more than 5-fold (from 0.17 (0.13; 0.24) to 1.30 (0.91; 1.37) mmol/L) increase of its level in snail’s haemolymph. This effect was shot-term. No longer than 2 h after normalization of conditions (removal of animals in «pure» aquarium water) haemolymph glucose level return to the initial (0.14 (0.10; 0.22) mmol/L), being stable in next twenty-four hours (0.20 (0.15; 0.29) mmol/L). Glucose water solution (10 mmol/L) was ineffective in producing experimental hyperglycemia in haemolymph of Lymnaea stagnalis.